Calibration and Temperature Compensation of a Low-Cost Capacitive Soil Moisture Sensor for Precision Irrigation in Thailand - Chulee, Napassakorn; Suebsaiprom, Pichet; Engkaninan, Anumat; Chompuchan, Chuphan (Engineering, Technology & Applied Science Research, 2025)
Low-cost capacitive soil moisture sensors have potential application in precision irrigation in Thailand. However, these sensors require proper calibration and are affected by soil temperature fluctuations that reduce their measurement accuracy. This study developed and validated a combined calibration and temperature compensation approach for the commercially available soil stick sensor. The calibration was performed using soil samples ranging from sandy clay loam to silty clay. A temperature compensation equation was developed by measuring the sensor responses under varying soil temperatures and moisture content levels in outdoor conditions. The sensor performance was assessed against a reference Time-Domain Reflectometry (TDR) sensor (TRIME-PICO64) and evaluated based on continuous field measurements for 14 days. The temperature compensation equation reduced the diurnal temperature effects through a linear correction model. The calibration showed a piecewise linear relationship between the Relative Voltage (VR) and volumetric water content (qV) with a strong correlation. The performance of the calibrated soil stick sensor was comparable to the TDR sensor, with the Confidence Index values exceeding 0.8. These findings indicated that the calibrated and temperature-compensated low-cost capacitive sensors could provide accurate soil moisture measurements for precise irrigation scheduling.